Ecological risk indices for heavy metals in the Morrocoy National Park: A study on recreational use - Centeno Bordones, Guillermo (2025)
Morrocoy National Park (MNP), located in the State of Falcón (Venezuela), is one of the main tourist destinations in the country. This study aims to determine the potential ecological risk indices for heavy metals in October 2023 in intertidal beach sediments, taking into account tourist load. Sediment samples were collected from Sombrero Key, the area with the highest tourist load (exceeding the others by 2.5 times); Sal Key, an area with a medium tourist load (by 2 times); and Borracho Key, an area with no tourist load (0). Physicochemical parameters, including pH, electrical conductivity, salinity, organic matter, granulometry, and heavy metal concentration, were considered in the analysis of the samples. Potential ecological risk indices (PERI) were calculated. Results show that pH and organic matter content are affected by tourist load, with the majority of sediments classified as fine. Heavy metal concentration was found in the following sequence: Fe > Mn > Cr > Ni > Cu > Pb > Cd. Regarding PLI, values did not exceed pollution estimates. PERC was low ecological risk for Cu ˃ Cr ˃ Pb and moderate risk for Cd. At the same time, PERI was classified as a low ecological risk for Borracho Key, close to moderate for Sal Key, and moderate for Sombrero Key. All these indices demonstrate the impact of tourist load on the MNP keys.